Incidental lung findings in a COVID-19 patient on 18F-FDG PET/CT done for preoperative evaluation of Marjolin's ulcer-first report from Chhattisgarh - Mudalsha Ravina; Tridip Dutta Baruah; Tinu Lukose; Ranganath T. Ganga; Amal Moideen (World Journal of Nuclear Medicine)
The aim of this case is to illustrate the 18F-fluorodeoxyglucose (FDG) positron emission tomography-computed tomography findings of a patient who was admitted in AIIMS, Raipur, for the preoperative evaluation of Marjolin ulcer and was later diagnosed with COVID-19 infection. Apart from the primary lesion in the right foot and pelvic lymph nodes, the scan revealed mild FDG-avid basal ground-glass opacities in bilateral lung fields with mediastinal and hilar lymph nodal involvement, in an otherwise asymptomatic patient.